2017
DOI: 10.4236/ojanes.2017.71001
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Intraoperative Goal-Directed Therapy Using the FloTrac/Vigileo System: An Analysis of Its Usefulness and Safety

Abstract: Purpose: We investigated whether the simplified intraoperative Goal-Directed Therapy (GDT) could improve the factors affecting medical costs, and contribute in standardizing intraoperative fluid management. Methods: The enrolled patients underwent esophagectomy, pancreatoduodenectomy, or aortic stent grafting in 2012, and between March 2013 and October 2014. We conducted a comparison study on the effects of GDT, between the before-GDT historical control group (n = 100) and GDT group (n = 100). The hemodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…25 Previous studies using goal-directed (GD) hemodynamic intervention in low-to-moderate risk patients undergoing major surgeries have failed to differentiate between the groups. 26 Ito et al, 27 in patients with risk profiles similar to ours, demonstrated improved global oxygen delivery and tissue oxygenation in the GrI: barring a decrease in acute kidney injury, complication rates between groups.…”
Section: Outcome Parameterssupporting
confidence: 74%
“…25 Previous studies using goal-directed (GD) hemodynamic intervention in low-to-moderate risk patients undergoing major surgeries have failed to differentiate between the groups. 26 Ito et al, 27 in patients with risk profiles similar to ours, demonstrated improved global oxygen delivery and tissue oxygenation in the GrI: barring a decrease in acute kidney injury, complication rates between groups.…”
Section: Outcome Parameterssupporting
confidence: 74%